Comment on “Short-lived pause in Central California subsidence after heavy winter precipitation of 2017” by K. D. Murray and R. B. Lohman - Shirzaei, Manoochehr (Sci Adv, 2019)
In a study by Murray and Lohman (M&L), the authors suggest that remote sensing data are useful for monitoring land subsidence due to aquifer system compaction. We agree. To infer aquifer dynamics, we provide a more detailed and joint analysis of deformation and groundwater data. Investigating well data in the Tulare Basin, we find that groundwater levels stabilized before 2015 and show that M&L’s observed continued subsidence through July 2016 is likely caused by the delayed compaction of the aquitard. Our analysis suggests the observed 2017 transient uplift is not due to recharge of the aquifer system after heavy winter rainfall because it requires an unrealistic vertical hydraulic gradient nearly five orders of magnitude larger than that typical of Tulare Basin. We find that, regardless of the amount of rainfall, transient annual uplifts of ~3 cm occur in May to June. Using an elastic skeletal storage coefficient of 5 × 10(−3), we link this ground uplift to annual groundwater level changes.